RNA interference activity of single-stranded oligonucleotides linked between the passenger strand and the guide strand with an aryl phosphate linker. (3rd June 2021) - Koizumi, Makoto; Hirota, Yasuhide; Nakayama, Makiko; Tamura, Masakazu; Obuchi, Wataru
Abstract: Recently, we demonstrated that asymmetrical 18 base-paired double-strand oligonucleotides comprised of alternately combined 2'- O -methyl RNA and DNA, termed MED-siRNAs, show high RNase resistance, efficient cleavage of target mRNA, and the subsequent reduction of target protein expression. The 5'-terminal phosphate group and the 3'-overhang of the guide strand were required to fully activate the RNAi activity of MED-siRNAs. Here, we evaluated MED-siRNAs modified with aryl phosphate groups at the 5'-end of the guide strand. The 5'-aryl phosphorylated MED-siRNAs showed highly efficient reduction of target protein expression comparable to 5'-phosphorylated MED-siRNAs. Moreover, 5'-aryl phosphorylated MED-siRNAs linked between the aryl phosphate group at the 5'-end of the guide strand and the hydroxyl group at the 3'-end of the passenger strand with alkyl amide linkers or peptides (e.g., DL-Ser-L-Ala-L-Tyr), resulted in single-stranded MED-siRNAs with a highly efficient cleavage activity of target mRNA with binding to Argonaute 2 via an RNA interference mechanism. These linker techniques could also be used to create siRNAs composed of naturally-occurring molecules such as amino acids. These findings suggest the possibility of using these single-stranded MED-siRNAs as siRNA reagents. Supplemental data for this article is available online at https://doi.org/10.1080/15257770.2021.1927077 .